Utility of Direct Pancreatic Function Testing in Children. Issue 2 (February 2017) - Alfaro Cruz, Ligia; Parniczky, Andrea; Mayhew, Allison; Hornung, Lindsey N.; Lin, Tom K.; Palermo, Joseph J.; Jackson, Kimberly; Abu-El-Haija, Maisam
Abstract : Objectives: Exocrine pancreatic insufficiency (EPI) can have a significant impact on a child's growth and nutrition. Our aim was to evaluate the utility of direct endoscopic pancreatic function testing (ePFT) in pediatrics. Methods: A single-center retrospective chart review was performed of children who underwent ePFT from December 2007 through February 2015. Endoscopic pancreatic function testings were performed by 1 of 2 methods: (1) intravenous cholecystokinin, followed by the collection of a single duodenal aspirate at 10 minutes, or (2) intravenous cholecystokinin or secretin, followed by the collection of 3 duodenal aspirates at a 5, 10, and 15 minutes. Samples were tested for pH and enzyme activities. Results: A total of 508 ePFTs were performed (481 single-sample tests, 27 multiple-sample tests). Based on the multiple-sample group, enzyme levels for chymotrypsin, amylase, and lipase peaked at 5 minutes, followed by a decrease in activity over time. Exocrine pancreatic sufficiency was identified in 373 (73.4%) and EPI in 93 (18.3%). Exocrine pancreatic sufficiency analysis found all pancreatic enzyme activities significantly increase with age: trypsin, chymotrypsin, amylase, and lipase, ( P < 0.05). Conclusions: Endoscopic pancreatic function testing can be used in the evaluation of EPI in children. Normative data suggest that pancreatic enzyme activities mature with age. Abstract : Supplemental digital content is available in the text.